Digitalization of guest record management through a web-based information system to support security and efficiency - Mawadah, Helvina Salsabila; Prabukusumo, M Azhar; Saputra, Bagus Hendra (Institute of Computer Science (IOCS), 2025)
Digitization of visitor registration improves efficiency and security in visit management in many institutions. This project seeks to create a web-based information system that replaces manual registration techniques to reduce the possibility of data loss and inaccuracy of registration, while increasing the efficiency and accuracy of guest information processing. The study used a software development methodology that leverages the Rapid Application Development (RAD) concept, which facilitates rapid and adaptive system development. The novelty of this system lies in its integration of automated blacklist detection and personalized notification workflows, features that are not commonly found in prior visitor registration systems. The system was designed and implemented specifically within an institutional environment but has the potential to be generalized and adapted for diverse organizational contexts, including government offices, corporate facilities, and educational institutions. The study results show that the web-based information system improves efficiency in visitor registration through automated verification, real-time monitoring, and notification integration, thereby facilitating safer and more organized guest management. This solution aims to enable institutions to improve their visitor reception processes, strengthen workplace security, and facilitate digital transformation in visit management.